Effects of Varying Degrees of Renal Impairment on the Pharmacokinetics of Duloxetine: Analysis of a Single-Dose Phase I Study and Pooled Steady-State Data from Phase II/III Trials - Lobo, Evelyn D.; Heathman, Michael; Kuan, Han-Yi; Reddy, Shobha; O’Brien, Lisa; Gonzales, Celedon; Skinner, Michael; Knadler, Mary Pat (Clinical pharmacokinetics, 2010)
Background Duloxetine is indicated for patients with a variety of conditions, and some of these patients may have mild to moderate degrees of renal impairment. Renal impairment may affect the pharmacokinetics of a drug by causing changes in absorption, distribution, protein binding, renal excretion or nonrenal clearance. As duloxetine is highly bound to plasma proteins and its metabolites are renally excreted, it is prudent to evaluate the effect of renal insufficiency on exposure to duloxetine and its metabolites in the systemic circulation. Objective The aim of this study was to evaluate the effects of varying degrees of renal impairment on duloxetine pharmacokinetics in a single-dose phase I study and using pooled steady-state pharmacokinetic data from phase II/III trials. Methods In the phase I study, a single oral dose of duloxetine 60 mg was given to 12 subjects with end-stage renal disease (ESRD) and 12 matched healthy control subjects. In the phase II/III trials (n = 463 patients), duloxetine 20–60 mg was given as once- or twice-daily doses. Duloxetine and metabolite concentrations in plasma were determined using liquid chromatography with tandem mass spectrometry. Noncompartmental methods (phase I: duloxetine and its metabolites) and population modelling methods (phase II/III: duloxetine) were used to analyse the pharmacokinetic data. Results The maximum plasma concentration (C max ) and the area under the plasma concentration-time curve (AUC) of duloxetine were ∼2-fold higher in subjects with ESRD than in healthy subjects, which appeared to reflect an increase in oral bioavailability. The C max and AUC of two major inactive conjugated metabolites were as much as 2- and 9-fold higher, respectively, reflecting reduced renal clearance of these metabolites. Population pharmacokinetic results indicated that mild or moderate renal impairment, assessed by creatinine clearance (CL CR ) calculated according to the Cockcroft-Gault formula, did not have a statistically significant effect on pharmacokinetic parameters of duloxetine. Values for the apparent total body clearance of duloxetine from plasma after oral administration (CL/F) in subjects with ESRD were similar to CL/F values in patients with normal renal function or with mild or moderate renal impairment. Conclusion Dose adjustments for duloxetine are not necessary for patients with mild or moderate renal impairment (CL cr ≥30 mL/min). For patients with ESRD or severe renal impairment (CL cr <30 mL/min), exposures of duloxetine and its metabolites are expected to increase; therefore, duloxetine is not generally recommended for these patients.